Research on large deflection deformation reconstruction of elastic thin plate based on strain monitoring. (January 2020) - Wang, Wenrui; Lu, Yu; Zhao, Dezong; Zhang, Jiaming; Bai, Xuesong
Highlights: A new deformation measurement method based on strain monitoring is proposed. Large deflection deformation of elastic thin plate with four-sided fixed. The theoretical solution for large deflection deformation based on strain information is proposed. Obtaining the strain and deformation of the whole surface by strain sensor array. Abstract: In this paper, a method of reconstruction deformation by measuring surface strain is proposed. Aiming at large deflection deformation of the four-sided fixed elastic thin plate structure, an algorithm for reconstructing deformation field based on surface strain monitoring is developed. The reconstruction method theoretically analyzes the thin elastic plate according to the large deflection deformation hypothesis and elastic mechanics. The experimental platform for strain monitoring of thin plate and several different loading conditions was established. Based on the analytic solution of deformation and strain from experimental, the deformation surface diagram of thin plates under different loads are obtained. The experimental results show that the average error of reconstruction of the elastic thin plate structure is 4.9%. This measurement method obtains deformation indirectly by measuring strain, and does not need to use too much space to install measuring equipment.